2018
DOI: 10.1021/acsami.8b01298
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Safety of Lithium-Ion Battery via a Redox Shuttle Additive 2,5-Di-tert-butyl-1,4-bis(2-methoxyethoxy)benzene (DBBB)

Abstract: 2,5-Di- tert-butyl-1,4-bis(2-methoxyethoxy)benzene (DBBB) is studied as a redox shuttle additive for overcharge protection for a 1.5 Ah graphite/C-LFP lithium-ion pouch cell for the first time. The electrochemical performance demonstrated that the protecting additive remains inert during the extended standard cycling for 4000 cycles. When a 100% overcharge is introduced in the charging protocol, the baseline cell fails rapidly during the first abusive event, whereas the cell containing DBBB additive withstands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
1
21
1
Order By: Relevance
“…reported on a battery with redox molecules being oxidized at the cathode upon overcharging, diffusing to the graphite‐based anode, and being reduced at the anode despite the existence of the SEI. [ 61 ] Indeed, the charge flow while overcharging observed in this experimental study is too high to be caused by an oxidation of all redox molecules in the electrolyte at the cathode and a Li intercalation into the anode, since the charge flow would stop after oxidation of all redox molecules (see the Supporting information). Accordingly, a redox shuttle mechanism seems likely.…”
Section: Discussionmentioning
confidence: 92%
“…reported on a battery with redox molecules being oxidized at the cathode upon overcharging, diffusing to the graphite‐based anode, and being reduced at the anode despite the existence of the SEI. [ 61 ] Indeed, the charge flow while overcharging observed in this experimental study is too high to be caused by an oxidation of all redox molecules in the electrolyte at the cathode and a Li intercalation into the anode, since the charge flow would stop after oxidation of all redox molecules (see the Supporting information). Accordingly, a redox shuttle mechanism seems likely.…”
Section: Discussionmentioning
confidence: 92%
“…This is because of a low rate and resultant partial reduction of Fe 3+ in LiFePO 4 at the electrolyte–electrode interface. This is often observed in other organic polymer–LiFePO 4 systems, and chemical/engineering optimization is required to reduce the overcharge. Although the tested current density was small, the demonstration in all-solid-state at 100 °C proves that COF-PEO- x -Li can act as solid-state Li electrolytes having sufficient thermal/chemical/mechanical properties.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, transport selectivities seem to play an important role for overcharge‐protection in lithium‐ion batteries. Several groups reported that overcharge‐protection additives, which are redox molecules, work successfully in conventional lithium‐ion batteries. In these batteries, overcharging leads to oxidation of the redox molecules at the positive electrode, diffusion of the redox molecules to the negative electrode and reduction of the redox molecules at the negative electrode, despite the existence of the SEI.…”
Section: Resultsmentioning
confidence: 99%